Sodium palatability in male spontaneously hypertensive rats - Pereira, E. D. [UNESP]; Faria, A. M.; Andrade-Franzé, G. M.F. [UNESP]; Menani, J. V. [UNESP]; De Luca, L. A. [UNESP]; Andrade, C. A.F. [UNESP] (Elsevier, 2021)
Spontaneously hypertensive rats (SHRs) ingest more NaCl than normotensive strains. Here we investigated NaCl intake and taste reactivity in adult male SHRs and normotensive Holtzman rats treated or not with AT1 receptor antagonist centrally in euhydrated condition and after fluid depletion. Taste reactivity was measured by the number of orofacial expressions to intra-oral infusions of 0.3 M NaCl. In euhydrated condition, intra-oral infusions of 0.3 M NaCl produced greater number of hedonic responses in SHRs than in normotensive rats, without differences in the number of aversive responses. Compared to euhydrated condition, the treatment with the diuretic furosemide + low dose of captopril (angiotensin converting enzyme blocker) increased the number of hedonic and reduced the number of aversive responses to intra-oral NaCl in normotensive rats, without changing the number of hedonic or aversive responses in SHRs. Losartan (AT1 receptor antagonist, 100 ng/1 μl) injected intracerebroventricularly in SHRs abolished 0.3 M NaCl intake induced by water deprivation + partial rehydration, whereas only transiently (first 30 min of the 60 min test) reduced hedonic responses, without changes in aversive responses to intra-oral NaCl. Losartan intracerebroventricularly also only transiently (first 30 min) reduced the number of hedonic responses to intra-oral NaCl in euhydrated SHRs. The results suggest that NaCl palatability is increased and independent from body fluid balance in SHRs. The results also suggest that central AT1 receptors are part of the mechanisms activated to increase NaCl intake and palatability in SHRs. A partial dissociation between NaCl intake and palatability in SHRs is also suggested.
Keywords: Angiotensin; Hypertension; Sodium appetite; Taste; Water deprivation